2014
DOI: 10.4049/jimmunol.1303144
|View full text |Cite
|
Sign up to set email alerts
|

S100A4 and Uric Acid Promote Mesenchymal Stromal Cell Induction of IL-10+/IDO+ Lymphocytes

Abstract: Simple stress or necrotic cell death with subsequent release of damage-associated molecular patterns (DAMPs) is a characteristic feature of most advanced tumors. DAMPs within the tumor microenvironment stimulate tumor-associated cells, including dendritic cells and mesenchymal stromal cells (MSCs). The presence of tumor-infiltrating MSCs is associated with tumor progression and metastasis. Oxidized necrotic material loses its stimulatory capacity for MSCs. As a DAMP, S100A4 is sensitive to oxidation whereas ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…Specifically, we found that IPF MPCs express higher levels of S100A4 compared with control MPCs (14). S100A4, a calcium binding protein, is upregulated in cancer stem cells, where it controls proliferation, differentiation, and metastasis (15)(16)(17)(18)(19)(20)(21)(22). S100A4 also amplifies TGF-β-induced fibroblast activation in the progressive fibrotic disorder systemic sclerosis (23).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Specifically, we found that IPF MPCs express higher levels of S100A4 compared with control MPCs (14). S100A4, a calcium binding protein, is upregulated in cancer stem cells, where it controls proliferation, differentiation, and metastasis (15)(16)(17)(18)(19)(20)(21)(22). S100A4 also amplifies TGF-β-induced fibroblast activation in the progressive fibrotic disorder systemic sclerosis (23).…”
Section: Introductionmentioning
confidence: 84%
“…While important, these studies are beyond the scope of the current body of work. S100A4 has also been termed metastasin because it regulates cancer cell metastasis (15)(16)(17)(18)(19)(20)(21)(22). While S100A4 levels are elevated in both cancer cells and IPF cells, IPF cells do not metastasize, suggesting that there are important differences between cancer and fibrosis in relation to S100A4 function.…”
Section: Discussionmentioning
confidence: 99%
“…It is constitutively present in all cells, but its levels increase following cell injury (63). It is the end product of purine nucleotide breakdown (64). Dying cells release uric acid extracellularly, which is then able to evoke immune responses such as the induction of dendritic cell maturation and increase in priming of CD8 T-cell responses to cross-presented antigens (65).…”
Section: Tablementioning
confidence: 99%
“…Nevertheless, an increasing body of evidence highlights the role of uric acid in diseases such as chronic kidney disease (11), fatty liver disease (12), cardiorenal syndrome and hypertension (13,14), coronary heart disease (15,16), type 2 diabetes (17), aging (18), and cancer (19), in addition to gout. The many associations of uric acid with common inflammatory diseases lead to a scenario of thrifty genes that currently predispose to fat storage disorders and systemic comorbidities (20).…”
mentioning
confidence: 99%